(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation: This article examines the linguistic features of ecological terminology in English and Uzbek, focusing on their structural, semantic, and functional aspects. The study highlights the differences and similarities in term formation, borrowing processes, and adaptation strategies in both languages. By analyzing ecological terms, the research provides insights into how languages evolve to accommodate scientific concepts, emphasizing the role of linguistic and cultural factors in terminology development.